Assessment through technology in the choral classroom - Dixon, Kira Leigh (Kansas State University, 2013)
Teaching a large performing ensemble class, such as choir, can make it difficult to keep a record of each student’s individual progress. This report will discuss my philosophy of music education along with ways to incorporate technology into student assessment. Technology can most benefit the educational process when it is easy and efficient. Through personal experience, incorporating technology into student assessment can be done in the four different methods explored in this report. These four methods are: integrating practice file submissions through a virtual interface; using Google Docs Surveys for self-reflection; incorporating audio or video recording students for sight-reading tests; and using YouTube for students to post videos for final projects. Each has the potential to both strengthen and organize the way student assessment is completed.
Keywords: Assessment technology choir choral; Music (0413); Music Education (0522)